Anthelminthic Efficacy of Chili (Capsicum annum longum) and Nutritional Supplementation on Ovine Fascioliasis in Ethiopia - Endris Feki Ahmed; Kanchana Markvichitr; Sornthep Tumwasorn; Skorn Koonawootrittriron; Apassara Choothesa; Sathaporn Jittapalapong (Agriculture and Natural Resources, 2007)
A 90 days study was conducted in Gewane Agricultural Technical and Vocational Education Training College, Ethiopia, to compare the anthelminthic effect of chili or Mitmita (Capsicum annum longum) and a conventional treatment such as Tricalbendazole on Fasciola infections to nutritional levels. A total of 72 Afar and Blackhead local breeds of sheep naturally infected by fascioliasis were randomly allotted into 3 groups, two nutrition levels (supplemented with wheat middling, cotton seed cake, corn, lime and common salt and not supplemented group) and three section treatments. One treatment group received 10 mg/kg of Tricalbendazole drenching orally on the 1, 21, and 42 days during the study period. The second group received 100 gm of crushed or chopped chili solution drenching orally on the 1, 21, and 42 days during the experimental period and the control group received no treatment. The control group divided into two groups of supplemented and not supplemented or grazing only. The treatment efficacy was assessed using the percentage of the egg or fluke reduction, body weight gain, blood parameters results post treatment on 30, 60 and 90 days. At the end of the experiment, animals were slaughtered and postmortem were performed for adult Fasciola recovery in the liver. Tricalbendazole and chili treated groups of animals had an efficacy of 100% and 84%, respectively. Animals treated by Tricalbendazole and chill in addition supplementation had high reduction of fecal egg count (FEC) compared to the treatment groups with no supplementation (p<0.05). No significant difference within treatments between two breeds was observed. The result indicated that chili could be an alternative treatment for subclinical ovine fascioliasis to alleviate the production loss in sheep herds.